2014
DOI: 10.1038/ncomms6200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular channels formed by subpopulations of PECAM1+ melanoma cells

Abstract: Targeting the vasculature remains a promising approach for treating solid tumors; however, the mechanisms of tumor neovascularization are diverse and complex. Here we uncover a new subpopulation of melanoma cells that express the vascular cell adhesion molecule PECAM1, but not VEGFR-2, and participate in a PECAM1-dependent form of vasculogenic mimicry (VM). Clonally-derived PECAM1+ tumor cells coalesce to form PECAM1-dependent networks in vitro and they generate well-perfused, VEGF-independent channels in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 57 publications
(53 reference statements)
1
61
0
Order By: Relevance
“…Recent studies show that subsets of glioma and melanoma cells (especially stem-like tumor cells) are able to switch on certain EC markers and transdifferentiate into vascular ECs (61)(62)(63)(64)(65). Such tumor-derived ECs participate in vascularization to ensure a steady supply of oxygen and nutrients for tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that subsets of glioma and melanoma cells (especially stem-like tumor cells) are able to switch on certain EC markers and transdifferentiate into vascular ECs (61)(62)(63)(64)(65). Such tumor-derived ECs participate in vascularization to ensure a steady supply of oxygen and nutrients for tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-borne cancers for example provide evidence that subclones display functional differences between each other when tested in mouse tumor models (21). Once identified, such subpopulations can be subjected to downstream analysis to elucidate cellular function (22). Some large-scale screening campaigns of cancer cell lines identified a range of potential surface markers that can be used in this fashion (23).…”
Section: Introductionmentioning
confidence: 99%
“…Dudley's group described a CD31 positive cutaneous melanoma cell population that was also positive for the melanocytic marker Tyr. These CD31+/Tyr+ VM-competent tumor cells existed as stable, yet hidden subpopulations in heterogeneous melanomas [50]. The population of CD31+ cells described in this study is different in that they originally observed during heart development where a population of endocardial cells differentiated into mesenchymal heart cushion cells forming cardiac septa and valves [52].…”
Section: Discussionmentioning
confidence: 82%
“…The first evidence of EMT in cancer was noted by studies demonstrating that invasiveness and adoption of a fibroblast morphology can be achieved by down regulation of E-cadherin expression in various epithelial cancer cell lines [50,51].…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%
See 1 more Smart Citation